Este Futuro es Otro Futuro: The role of social discourse on the [under]development of contemporary academic electronic music in Perú - López Ramírez Gastón, José Ignacio (2020)
Descargue el documento en el repositorio de la Universidad de California, San Diego: https://escholarship.org/uc/item/2sm8k2dk